2021
DOI: 10.1002/slct.202103141
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Approach to Access Multi‐Substituted Indenes via Nazarov Cyclisation of Aryl, Vinyl, and Alkyl/Aryl Carbinols

Abstract: A divergent approach to highly substituted functionalized indenes has been developed. The two‐step reaction involving nucleophilic addition reaction of aryl vinyl ketone, an ideal intermediate with aryl or alkyl nucleophilic reagent, followed by electrocyclic reaction (Nazarov cyclization) in the presence of Lewis acid catalyst afforded indene derivatives in good to excellent yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Modern variations of this process have found different ways of accessing the key pentadienyl cation intermediate, 3 including through dehydration of divinyl alcohols to form substituted cyclopentadienes (Scheme 1a). 4 However, this strategy has rarely been extended to the synthesis of five-membered heterocycles. Würthwein and co-workers reported that α-hydroxy-β,γ-unsaturated oximes undergo dehydration in the presence of stoichiometric triflic acid to form 1-azapentadienyl cations, with subsequent electrocyclisation giving trisubstituted pyrroles.…”
Section: Introductionmentioning
confidence: 99%
“…Modern variations of this process have found different ways of accessing the key pentadienyl cation intermediate, 3 including through dehydration of divinyl alcohols to form substituted cyclopentadienes (Scheme 1a). 4 However, this strategy has rarely been extended to the synthesis of five-membered heterocycles. Würthwein and co-workers reported that α-hydroxy-β,γ-unsaturated oximes undergo dehydration in the presence of stoichiometric triflic acid to form 1-azapentadienyl cations, with subsequent electrocyclisation giving trisubstituted pyrroles.…”
Section: Introductionmentioning
confidence: 99%